2013
DOI: 10.1002/jlcr.3074
|View full text |Cite
|
Sign up to set email alerts
|

Labeling of benzodioxin piperazines with fluorine‐18 as prospective radioligands for selective imaging of dopamine D4 receptors

Abstract: The D(4) receptor is of high interest for research and clinical application but puts high demands on appropriate radioligands to be useful tools for investigation. Search for adequate radioligands suitable for in vivo imaging is therefore still in progress. The potential neuroleptic drug 6-(4-[4-fluorobenzyl]piperazin-1-yl)benzodioxin shows high affinity and selectivity to the D(4) receptor. Derivatization of this lead structure by adding hydrophilic moieties was carried out in order to lower its lipophilicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…The same research group has demonstrated high radiochemical conversion using the pyridine derivative by halogen (Cl) exchange. 5 More challenging fluorine-18 labelings at the meta-position to prepare 3-[ 18 F]fluorobenzaldehydes have also been reported by our 7 and other groups from a variety of precursors. [8][9][10] Recently, Richarz et al reported fluorine-18 labeled benzaldehydes according to the "minimalist" radiolabeling protocol, without base and azeotropic drying of [ 18 F]fluoride.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…The same research group has demonstrated high radiochemical conversion using the pyridine derivative by halogen (Cl) exchange. 5 More challenging fluorine-18 labelings at the meta-position to prepare 3-[ 18 F]fluorobenzaldehydes have also been reported by our 7 and other groups from a variety of precursors. [8][9][10] Recently, Richarz et al reported fluorine-18 labeled benzaldehydes according to the "minimalist" radiolabeling protocol, without base and azeotropic drying of [ 18 F]fluoride.…”
Section: Introductionsupporting
confidence: 60%
“…A variety of prosthetic groups containing aldehyde functionalities have been developed . Kugler et al and Lemaire et al reported labeling of 4‐fluorobenzaldehydes and 2‐fluorobenzaldehydes and compared the radiolabeling efficiencies of nitro‐ and trimethylammonium triflate‐ precursors . Although conversions were comparable, the reaction was much faster for the trimethylammonium triflate precursors.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A wellknown reaction for aldehydes is the aldol condensation, which has been used in the synthesis of PET tracers with the dibenzalacetone core structure, as can be seen in Section 3. 243,244 Comparable conversions were observed for both leaving groups, however reactions were in general faster for the trimethylammonium triflate containing precursors (5 minutes versus 15 minutes respectively).…”
Section: [ 18 F]fluorobenzaldehydesmentioning
confidence: 93%